Penatalaksanaan Status Epileptikus dengan Infeksi Sistem Saraf Pusat di Unit Perawatan Intensif: Laporan Kasus: Laporan Kasus - Akhsaniati, Novi Dwi; Adiyanto, Bowo (Cermin Dunia Kedokteran, 2026)
Introduction: Status epilepticus (SE) is a critical neurological emergency characterized by prolonged seizure activity that poses significant neurological risks and death, requiring immediate and effective management to prevent morbidity and mortality. SE can result from a variety of causes, including primary neurological disorders, metabolic disturbances, and iatrogenic factors. In the ICU, drug toxicity and electrolyte imbalances are common triggers, accounting for over 30%−35% of seizures. Understanding the underlying causes, such as central nervous system infections or autoimmune encephalitis, is crucial for targeted treatment and improving patient outcomes. Case: A 21-yearold male with SE complicated by a central nervous system (CNS) infection was managed in the intensive care unit (ICU). Seizure control was achieved using continuous infusions of midazolam and phenytoin. The treatment strategy also included supportive care, including mechanical ventilation and hemodynamic stabilization with norepinephrine. The patient's condition improved significantly. Discussion: This case demonstrates that favorable clinical outcomes in SE complicated by a CNS infection rely heavily on continuous sedation, the selection of antibiotics with adequate CNS penetration (such as linezolid), and meticulous hemodynamic monitoring in the intensive care setting. Conclusion: This case highlights the importance of early diagnosis, targeted treatment, and interdisciplinary collaboration.